Digital Marketing Communication Strategy in Increasing Student Registration on the Juara Academy Platform - Jelita Ananda; Lies Utami Efni Safitri (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
The development of social media has driven changes in digital marketing communication strategies, including within educational institutions such as Juara Academy. This study aims to analyze digital marketing communication strategies through Instagram in increasing student enrollment, identify gaps between social media performance and conversion rates, and formulate efforts to optimize these strategies. This research employs a descriptive qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, and then analyzed using the interactive model of Miles and Huberman, as well as the AIDA framework (attention, interest, desire, action). The results indicate that digital marketing communication strategies have been systematically implemented through the utilization of Instagram features such as feed, story, reels, and live to capture attention, build interest, generate desire, and ultimately encourage enrollment actions. However, a gap was found between high engagement levels and suboptimal enrollment conversions, influenced by technical factors such as inconsistent content posting and a lack of integration across communication stages. Strategic optimization is therefore necessary through strengthening content consistency, enhancing more personalized interactions, and leveraging persuasive approaches based on audience experience. This study provides practical contributions to the management of digital marketing communication as well as theoretical contributions to the development of social media–based marketing communication studies.